Trichosporon Asahii Infection after Total Knee Arthroplasty: A Case Report and Review of the Literature - Qiang Zuo; Lele Dong; Weidong Mu; Lingyun Zhou; Tongping Hu; Hua Zhang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Reports of fungal infection after total knee arthroplasty are extremely rare. In most reports, the infecting organism is a Candida species. The present report describes a case involving a 73-year-old immunocompetent woman who underwent total knee arthroplasty and presented one month later with signs of prosthetic infection. She underwent joint debridement and the fluid was sent for culture and sensitivity testing. The culture showed growth of Trichosporon asahii. The patient was administered intravenous and intra-articular injections of amphotericin B, followed by antifungal treatment with voriconazole for one year. At 26 months of follow-up, there was no evidence of infection and the patient was ambulating with a walker. To the authors’ knowledge, the present case is the first report of T asahii infection following knee replacement. Early detection, prompt institution of the appropriate antibiotics and regular follow-up are recommended.